Rand McNally : children's atlas of world history - Rand McNally and Company (Chicago : Rand McNally and Company, 1991)
1. History 2. Reference books
"First published in 1988 by Kingfisher Books, Ltd."--P. opposite t.p.
Includes index.
Basic Ed. Students
Keywords: Historical geography -- Maps; Historical geography -- Maps; World history; Atlases